Pilot association study of the β-glucocerebrosidase N370S allele and Parkinson's disease in subjects of Jewish ethnicity - Clark, Lorraine N.; Nicolai, Angelique; Afridi, Shehla; Harris, Juliette; Mejia-Santana, Helen; Strug, Lisa; Cote, Lucien J.; Louis, Elan D.; Andrews, Howard; Waters, Cheryl; Ford, Blair; Frucht, Steven; et al. (Movement disorders, 2005)
Mutations in the β‐glucocerebrosidase gene cause Gaucher's disease, one of the most common lysosomal lipid storage diseases in the Ashkenazi Jewish population. The occurrence of parkinsonism in patients with Type 1 Gaucher's disease has been noted previously. In this pilot study, we evaluated a possible association between Parkinson's disease (PD) and the β‐glucocerebrosidase gene N370S allele (nt.1226 A>G) in 160 Parkinson's disease patients and 92 controls of Jewish ethnicity. We observed a higher frequency of the N370S genotype in PD cases (NS and SS, 10.7%) compared to controls (NS and SS 4.3%); however, the difference was not statistically significant (χ2 = 3.4, P = 0.2). A total of 17 PD cases carry the N370S allele, including 2 homozygotes and 15 heterozygotes. The N370S allele (nt.1226 A>G) may be associated with PD in patients of Jewish ethnicity and should be examined in a larger study. © 2004 Movement Disorder Society